Public religion and the urban environment : constructing a river town - Bohannon, Richard (Richard R.) (Continuum, 2011)
"Nature' and the 'city' have most often functioned as opposites within Western culture, a dichotomy that has been reinforced (and sometimes challenged) by religious images. Bohannon argues here that cities and natural environments, however, are both connected and continually affected by one another. He shows how such connections become overt during natural disasters, which disrupt the narratives people use to make sense of the world,including especially religious narratives, and make them more visible. This book offers both a theoretical exploration of the intersection of the city, nature, and religion, as well as a sociological analysis of the 1997 flood in Grand Forks, ND, USA. This case study shows how religious factors have influenced how the relationship between nature and the city is perceived, and in particular have helped to justify the urban control of nature. The narratives found in Grand Forks also reveal a broader understanding of the nature of Western cities, highlighting the potent and ethically-rich intersections between religion, cities and nature."--Bloomsbury Publishing.